2018
DOI: 10.1097/bpb.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral avulsion fracture of the anterior–superior iliac spine in a teenager: a case report with a literature review

Abstract: An anterior-superior iliac spine avulsion fracture is an uncommon injury in adolescent athletes and simultaneous bilateral avulsion fracture is fairly rare. The authors report cases of traumatic avulsion fractures of anterior-superior iliac spine after sports activity in teenagers. Open reduction and cannulate screws fixation resulted in an excellent functional outcome for this relatively uncommon fracture. The authors also stress the importance of careful clinical examination and recommend open reduction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…1). Following application of the inclusion and exclusion criteria, a total of 70 studies [2,5,12–79] (all levels IV–V) comprising 279 athletes with 286 apophyseal injuries were included. The weighted mean age of included athletes was 14.5 + 1.3 years (range, 8–18 years).…”
Section: Resultsmentioning
confidence: 99%
“…1). Following application of the inclusion and exclusion criteria, a total of 70 studies [2,5,12–79] (all levels IV–V) comprising 279 athletes with 286 apophyseal injuries were included. The weighted mean age of included athletes was 14.5 + 1.3 years (range, 8–18 years).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that 86% of patients with anterior fractures successfully respond to conservative treatment ( 24 ). However, the conservative treatment is not risk-free, the most frequent complications are exostosis formation, non-union and persistent pain ( 31 ). Occasionally, an anterior fracture requires additional surgical treatment when a patient's intractable pain fails to respond to conservative treatment or in the presence of large displacement of fracture ends that are not expected to heal spontaneously ( 32 ), as the case reported in our patient.…”
Section: Discussionmentioning
confidence: 99%